Physicochemical properties of guayabilla (Psidium guineense), myrtle (Psidium sartorianum) and guava (Psidium guajava) - Valera-Montero, Luis Lorenzo; Enríquez-Nava, Silvia; Silos-Espino, Héctor; Padilla-Ramírez, José Saúl; Perales Segovia, Catarino; Flores-Benítez, Silvia (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to determine the possible use of guayabilla (Psidium guineense) and myrtle (P. sartorianum) in innovation for the generation of food products, the physicochemical properties of fruits of these species were compared with those of guava (Psidium guajava). For this, five wild fruit collection sites were selected in the municipality of Talpa, Jalisco. The hypothesis was that the levels of citric acid and ripening index could be higher in guayabilla and myrtle, while the sugar content could be higher in guava. The experimental design used was a completely randomized one with a number of fruits that varied depending on the trees of the species present in each site. The obtained means were compared by the Tukey test p= 0.05. The acidity observed in mature fruits of Psidium sartorianum and Psidium guineense ranged between pH 2.84 to 3.21, while in guava a pH of 4.13 (less acidic) was observed. The titratable acidity obtained was congruent with the pH, since at lower values ​​of titratable acidity correspond the lower pH values. Despite the acidity of the fruits of Psidium sartorianum, one of the collection sites showed a total soluble solids index (7.4 °Brix) higher than that of guava (5.32 °Brix). The ripening index was higher for guava, in contrast to the low values found in Psidium guineense and Psidium sartorianum. Finally, Psidium guajava presented larger fruits than the two-wild species.
Keywords: Psidium guajava; Psidium guineense; Psidium sartorianum; antioxidant capacity; total soluble solids